Analisis Semantik Kosakata Dialek Kansai yang Trending di Aplikasi X: Semantic Analysis of Kansai Dialect Vocabulary Trending on the X Platform - Hanan Taufiequrrahman; Dwi Puspitosari (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
The development of digital technology has encouraged the spread of regional dialects into virtual spaces. This study examines the phenomenon of Kansai Dialect vocabulary usage that has become a trend on the X Platform as a form of language variation in digital communication. The aim of this study is to identify the dominant forms of Kansai Dialect vocabulary and analyse the processes of semantic change and linguistic adaptation. This research employs a descriptive qualitative approach with a sociolinguistic design. The data consist of posts on the X Platform in September 2025, which were analysed using theories of semantics and semantic change. The results show that four vocabulary items are the most dominant, namely honma, meccha, egui, and shaanai. These vocabulary items have undergone semantic adaptations, including shifts in emotional function, dialect standardisation, semantic amelioration, and changes in pragmatic function. This study concludes that the use of Kansai Dialect on social media functions not only as a means of information exchange but also as a medium for self-expression and the formation of social closeness.